Regionalisation of conceptual rainfall-runoff model parameters for predicting stream flows of ungauged catchments in the Blue Nile Basin [Abstract only] - Akawka, A. L.; Haile, Alemseged Tamiru (2014)
Better utilization of water resources depends on the level of understanding of the hydrology of a river basin. The understanding of the hydrology also depends on the extent to which the catchment is gauged. There are many catchments in the Blue Nile basin for which there are very little or no monitoring data available, thus the question as to whether it would be possible to extend and/or generalize model parameters obtained through calibration of gauged watersheds to ungauged catchments within the same region. This study explored the possibility of developing regionalized model parameter sets for use in ungauged catchments. The Blue Nile in the Ethiopian part is sub divided in to 16 sub-basins. In this study, except Dinder and Rahd the remaining 14 sub-basins were considered in the regionalization procedure. The HBV-96 rainfall-runoff model is used to perform the rainfall-runoff analysis. We calibrated HBV model for a number of gauged catchments in the basin. Among the calibrated catchments, 25 catchments were selected for regionalization purpose based on the criteria of relative volume error and Nash Sutcliffe values. For gauged and ungauged catchments, physical catchment characteristics (PCC) were extracted to establish a relationship with the model parameters (MPs) and develop regional model for estimating streamflow for ungauged catchments. The HBV-96 model is used to simulate the runoff from the ungauged catchments. Results from this study indicate that regionalized parameter sets for the HBV model can be obtained and used for making satisfactory hydrologic response predictions in ungauged catchments.